The Relationship between The Quality of Sleep and Learning Concentration among School-Age Children - Sri Wulandari Novianti; Meli Andriyani; Dwi Hastuti (Universitas Padjadjaran, 2022)
Parallel to the operational concrete development stage, school-age children start to develop their skills in logical thinking and problem-solving. They need adequate concentration to grow at the stage successfully. One of the determining factors in achieving such concentration is the quality of sleep. The study aims to analyze the relationship between sleep quality and learning concentration among school-age children. This research is a cross-sectional descriptive quantitative study. The samples were taken by proportional stratified random sampling from 53 respondents of 111 populations. Data were collected using PSQI and concentration questionnaires and analyzed using chi-square. The results indicated that 47 children (88.7 %) had a low sleep quality and 33 children (62.3 %) on a middle range of learning concentration. The statistical analysis showed 58.5 % of children with low sleep quality had a middle learning concentration level and 30.2 % had a low concentration level with a p-value (0.000) < value α (0.05). It can be concluded that there is a significant relationship between the quality of sleep and the level of learning concentration for school-age children at SD IT Al-Maqom Cimahi. Nurses as healthcare professionals can cooperate with the school to provide health education for the students and their parents regarding decent sleep quality and its effect on their growth and development, especially in studying. The parents can modify their children’s daily activities, especially before bedtime. One of them is rules about using gadgets and other electronic media in their bedrooms.